Religious Coping of Servants at GBI Jemaat Ayalon Kupang - ORA PAU, QUEENY VHALIN; Syamruth, Yendris Krisno; Ratu, Feronika (Journal of Health and Behavioral Science, 2025)
Religious coping is the way a person relies on faith, worship, and supportfrom their religious community to deal with life's pressures or challenges. Thepurpose of this study was to determine the religious coping of ministers at GBIAyalon Kupang related to understanding, application, and assessment of religiouscoping. The research method used is qualitative. The data collection technique is astructured interview. Sampling in this study used a purposive sampling techniquewith 5 participants. This study found that servants at GBI Ayalon Kupang facespiritual and interpersonal challenges, such as a crisis of faith, the declining spirit ofservice, and conflict within the ministry team. They overcome these challenges bystrengthening their relationship with God through prayer and seeking support fromothers and church leaders.